Female economic participation and dynamics of GDP per capitain eu member-states - Vinska, Oksana; Tokar, Volodymyr (Університет «КРОК», 2021)
The article sheds light on female emancipation in EU member-states being the magnet for Ukraine due to their living standards and values. The aim of the article is to analyze the economic activity of women and the dynamics of GDP per capita in EU member states. Gender equality is the integral part of EU internal and external policies being an overwhelming concept embracing many dimensions, including the economic one. The EU concentrates on engaging more femalesin the official labor market with guarantees of equal with males salaries, supporting work-life balance, voluntary and compulsory gender quotas in business and politics, ensuring safety for women at home and workplaces. A wide range of publications tries to persuade that there is a correlation between female economic emancipation and national economic advancement demonstrating that gender equality is only a new method guaranteeing additional profits for corporations and tax revenues for governments. The authors of this research paper apply Spearman coefficient to determine whether there is any correlation between economic growth and economic participation and opportunities for women, namely GDP per capita at current market prices and values of economic gender gap sub-index of EU member-states in 2016-2020. The average growth of GDP per capita in EU member-states equaled 11.6 percent in 2016-2020. Ireland showed the maximum relative increase of 29.1 percent, while Greece, Italy, Spain, and Sweden experienced the decline. The average gender gap in economic participation and opportunity in EU member-states decreased by 0.018 points in 2016-2020. The calculations show that the Spearman correlation coefficient is statistically insignificant. Therefore, economic gender equality by itself is not enough for stimulating economic growth and should be viewed as an indisputable human right and accompanied by fostering gender equality in other spheres, such as education, health care and politics

У статті розглядається емансипація жінок у країнах-членах ЄС, які є магнітом для України завдяки їхньому рівню життя та цінностям.Метою статті є аналіз економічної активності жінок та динаміки ВВП на душу населення в країнах-членах ЄС.Гендерна рівність є невід’ємною частиною внутрішньої та зовнішньої політики ЄС та потужною концепцією, що охоплює багато вимірів, включаючи економічний. ЄС концентрується на залученні більшої кількості жінок на офіційний ринок праці із гарантуванням рівних із чоловіками зарплат, підтримці балансу між роботою та особистим життям, добровільних та обов’язкових гендерних квотах у бізнесі та політиці, забезпеченні безпеки жінок вдома та на робочих місцях. Широкий спектр публікацій намагається переконати, що існує взаємозв’язок між емансипацією жінок та економічним розвитком, демонструючи, що гендерна рівність є лише новим методом, що гарантує додатковий прибуток для корпорацій та податкові надходження для урядів. Автори цього дослідження застосовують коефіцієнт Спірмена, щоб визначити, чи існує якась залежність між економічнимзростанням і покращенням економічних можливостей жінок, а саме між ВВП на душу населення в поточних ринкових цінах та значеннями субіндексу економічного гендерного розриву у країнах-членах ЄС у 2016-2020. Середній приріст ВВП на душу населення в країнах-членах ЄС у 2016-2020 рр. становив 11,6 відсотки. Ірландія продемонструвала максимальний відносний приріст у 29,1 відсотки, тоді як Греція, Італія, Іспанія та Швеція зазнали зниження. Середній гендерний розрив в економічній участі та можливостях у країнах-членах ЄС зменшився на 0,018 пунктів у 2016-2020 роках. Розрахунки показують, що коефіцієнт кореляції Спірмена є статистично незначущим. Отже, економічна гендерна рівність сама по собі є недостатньої для стимулювання економічного зростання, та її слід розглядати як безперечне право людини та поєднувати зі сприянням гендерній рівності в інших сферах, таких як освіта, охорона здоров’я та політика
Keywords: economic development; economic participation and opportunity; EU member-states; gender equality; gender gap; GDP per capita; економічний розвиток; економічна участь та можливості; країни-члени ЄС; гендерна рівність; гендерний розрив; ВВП на душу населення